2012
DOI: 10.1186/1471-2393-12-57
|View full text |Cite
|
Sign up to set email alerts
|

How good are we at implementing evidence to support the management of birth related perineal trauma? A UK wide survey of midwifery practice

Abstract: BackgroundThe accurate assessment and appropriate repair of birth related perineal trauma require high levels of skill and competency, with evidence based guideline recommendations available to inform UK midwifery practice. Implementation of guideline recommendations could reduce maternal morbidity associated with perineal trauma, which is commonly reported and persistent, with potential to deter women from a future vaginal birth. Despite evidence, limited attention is paid to this important aspect of midwifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 22 publications
7
59
2
Order By: Relevance
“…The difficulty surrounding the incorporation of evidence-based guidelines into clinical practice is not only evident with the persistent use of episiotomy, but is also seen in the management of perineal trauma. This phenomenon was highlighted in a cross-sectional study of British midwives who reported difficulties identifying and repairing perineal trauma (26) .…”
Section: Category Dmentioning
confidence: 99%
“…The difficulty surrounding the incorporation of evidence-based guidelines into clinical practice is not only evident with the persistent use of episiotomy, but is also seen in the management of perineal trauma. This phenomenon was highlighted in a cross-sectional study of British midwives who reported difficulties identifying and repairing perineal trauma (26) .…”
Section: Category Dmentioning
confidence: 99%
“…A study (6) published in 2012 focused on the inadequate classification of perineal trauma among professionals because the anatomical variables of the vulvoperineal region may interfere with this classification, especially in the case of third and fourth-degree lacerations, which are generally underestimated. The classification of perineal trauma has been proposed and accepted internationally, as follows: first-degree trauma (involves skin and mucosa), second-degree trauma (includes perineal muscles), third-degree trauma (involves the anal sphincter and is subclassified into 3a: damage to less than 50% of the external anal sphincter; 3b: damage to more than 50% of the external anal sphincter; 3c: damage to the entire internal and external anal sphincter and fourth-degree trauma (affects the anal epithelium) (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, after the generation, synthesis and transfer of evidence, evidence-based practices are implemented through the assessment of their impact on the healthcare process (2) . Over the past decades, research in maternal health has sought solutions to various problems, such as perineal trauma, defined as any damage to the genitalia during childbirth that occurs by spontaneous laceration or intentionally by surgical incision (episiotomy) (6) . It is estimated that approximately 70% of women having vaginal birth sustain some sort of perineal trauma, and three quarters of them will require suturing (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Only midwives with 20 years or more of experience and those with higher levels of qualification were more likely to implement evidencebased recommendations and felt more confident about perineal care (30) .…”
Section: Discussionmentioning
confidence: 99%